Mitochondrial Impairment in Sarcopenia - Francesco Bellanti; Aurelio Lo Buglio; Gianluigi Vendemiale (Biology, 2021)
Sarcopenia is defined by the age-related loss of skeletal muscle quality, which relies on mitochondrial homeostasis. During aging, several mitochondrial features such as bioenergetics, dynamics, biogenesis, and selective autophagy (mitophagy) are altered and impinge on protein homeostasis, resulting in loss of muscle mass and function. Thus, mitochondrial dysfunction contributes significantly to the complex pathogenesis of sarcopenia, and mitochondria are indicated as potential targets to prevent and treat this age-related condition. After a concise presentation of the age-related modifications in skeletal muscle quality and mitochondrial homeostasis, the present review summarizes the most relevant findings related to mitochondrial alterations in sarcopenia.